2021
DOI: 10.1200/po.21.00076
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Acquired Resistance Mutation MET D1228N to Crizotinib With Cabozantinib in NSCLC With MET Exon 14 Skipping Mutation

Abstract: The following represents disclosure information provided by the authors of this manuscript. All relationships are considered compensated unless otherwise noted. Relationships are self-held unless noted. I = Immediate Family Member, Inst = My Institution. Relationships may not relate to the subject matter of this manuscript. For more information about ASCO's conflict of interest policy, please refer to www.asco.org/rwc or ascopubs. org/po/author-center. Open Payments is a public database containing information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…60 Given the differential binding properties of type I and type II MET TKIs, resistance by acquired point mutations in the tyrosine kinase domain can be potentially overcome by switching to a different type of MET TKI. This strategy has been reported in several case reports, with patients achieving both stable disease and partial responses when switching from type Ib to type II inhibitors, such as cabozantinib or merestinib, in the setting of acquired MET mutations [59][60][61] and a partial response in a patient switching from a type II to a type Ia inhibitor in the setting of an acquired MET mutant-exon 14 allele amplification. 59 Given the biological rationale for this approach, there is an unmet need to conduct clinical trials that can shed a light on the optimal therapeutic sequencing strategy tailored according to resistance mechanisms.…”
Section: Resistance To Met Inhibitorsmentioning
confidence: 94%
“…60 Given the differential binding properties of type I and type II MET TKIs, resistance by acquired point mutations in the tyrosine kinase domain can be potentially overcome by switching to a different type of MET TKI. This strategy has been reported in several case reports, with patients achieving both stable disease and partial responses when switching from type Ib to type II inhibitors, such as cabozantinib or merestinib, in the setting of acquired MET mutations [59][60][61] and a partial response in a patient switching from a type II to a type Ia inhibitor in the setting of an acquired MET mutant-exon 14 allele amplification. 59 Given the biological rationale for this approach, there is an unmet need to conduct clinical trials that can shed a light on the optimal therapeutic sequencing strategy tailored according to resistance mechanisms.…”
Section: Resistance To Met Inhibitorsmentioning
confidence: 94%
“… 79 In our study, one patient exhibited responsiveness to savolitinib after exhibiting resistance to ensartinib. 61 In addition, cabozantinib reportedly can overcome crizotinib-induced resistance to the MET D1228N mutation, 80 and a patient with acquired MET Y1230C achieved PR with merestinib therapy after exhibiting resistance to crizotinib. 76 Moreover, preclinical studies have revealed that glesatinib and foretinib can overcome resistance induced by mutations of D1228N and Y1230C/H.…”
Section: Updated Landscapes Of Met Tkismentioning
confidence: 99%
“…Resistance mutations against type I MET inhibitors are sensitive to type II inhibitors, and vice versa [22][23][24][25][26]. In patients with METex14 NSCLC, cabozantinib can overcome resistance selected by type I MET inhibitors [27][28][29]. Furthermore, cabozantinib is effective in METex14-positive NSCLC with brain metastases [30].…”
Section: Preemptive Combination For Met-driven Nsclcmentioning
confidence: 99%